Vector Bond Graph Method of Kineto-static Analysis for Planar Multi-body System with Gear Pair - Wang Zhongshuang; Zhao Yanwei; Tao Yangyang; Cao Jianguo (Jixie chuandong)
In order to increase the reliability and efficiency of the kineto-static analysis of complex planar multi-body system,the corresponding vector bond graph method is proposed.According to the kinematic constraint condition,the vector bond graph model of a gear pair with arbitrary tooth profile of tooth is built.Based on this,the theoretical method to build the planar multi-body systems model with gear pair by vector bond graph is given.For the algebraic difficulties brought by differential causality and nonlinear junction structure in modeling and kineto-static analysis of planar multi-body systems with gear pair,the effective bond graph augment method is proposed.By the corresponding algorithm,the computer aided modeling and kineto-static analysis of planar multi-body system with gear pair on a computer is realized,the validity of this method is illustrated.